Correlation between lipid, cholesterol and fatty acid contents in the shoulder of castrated and non-castrated Santa Inês lambs - Cristiane Leal dos Santos-Cruz; Christian Albert Carvalho da Cruz; Thiago Ramos Lima; Juan Ramon Olalquiaga Pérez; Rodrigo Soares Junqueira; Braulio Crisanto Carvalho da Cruz (Revista Brasileira de Zootecnia, 2012)
The objective of this study was to establish a correlation between the content of total lipids, cholesterol and fatty acid profile of the edible portion of the shoulders of 12 castrated and 12 non-castrated Santa Ines lambs, slaughtered at different ages (84, 168, 210, 252 days). Shoulders and the edible portion (muscle and fat) were weighed and stored at -5 °C. Castrated and uncastrated lambs increased their body weight and half carcass weight, respectively. The shoulder weight increased in the carcasses of uncastrated animals. The edible portion of the shoulders of castrated lamb has greater amount of total lipids (16.09 g/100 g). The cholesterol content was influenced by castration, reducing with age. Santa Ines castrated lambs, under semi-extensive conditions, presented larger amounts of C18:1 T11 and CLA in the edible portion of the shoulder. Castration causes no significant correlation between total lipids, cholesterol and total saturated and unsaturated fatty acids of the edible portion of Santa Ines shoulder lambs from 84 to 252 days of age.